Aberration of the Wnt signaling pathway in pulmonary fatal adenocarcinoma: a case report - Li, Junzhe; Bai, Xinhua; Zou, Yufeng; Hao, Yanyong; Xu, Xianhua (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
We report a case of a 58-year-old woman showed a homogeneous well-defined perihilar mass in the right upper lobe and fully surrounded by aerated parenchyma at computed tomography (CT). A right upper lobectomy with mediastinal lymph node sampling was performed. A pathologic diagnosis of well-differentiated fetal adenocarcinoma of the lung was made and staged as T2bN0M0. For the expression of Wnt signaling pathway molecules, positive expressions of Wnt1, β-catenin, c-Myc, Cyclin D1and MMP7 were especially prominent in budding solid nests, but not in glandular structures. The nuclear/cytoplasmic localization of β-catenin accompanied upregulation of Wnt signaling pathway molecules in budding solid nests. These results demonstrated that elevated nuclear/cytoplasmic expression of β-catenin in fatal adenocarcinoma might be regulated by the Wnt signaling pathway.